Development of a Machine for Expressing Vernonia amygdalina Leaf Juice - Oke, A.O.; Koya, O.A.; Akanbi, C.T. (Ife Journal of Technology, 2015)
Vernonia amygdalina leaf juice is known for its nutritive value and as food supplement. There is therefore, a need for a simple processing device for the leaf juice expression. This study developed a machine for producing contamination-free V. amygdalina leaf juice. The design of the machine was based on the principle of a pressure deferential applied to the incoming leaf mash compared with that applied to the discharged material. Macerated leaves were compressed through a tapered screw conveyor; whose shaft terminates as a rising but short conical kink. The maximum juice yield of 41.39% was expressed from the leaf mash at pressing pressure and residence time of 6.09 MPa and 11 min, respectively. The throughput of the machine was 9.60 kg/h and the juice extraction rate was 1.86 /h at leaf to water ratio of 1: 0.8. The maximum juice expression efficiency was 15.54% at 1:1.2 leaf to water ratio, 60 rpm constant rotational motor speed and 11.99 kg/h feeding rate. Approximately 26.38% of the inherent moisture content of the leaf was expressed by the machine. It is expected that the machine may be used to express juice from other plant leaves having comparative physical properties. The machine therefore provides a viable technique for mechanical expression of good quality V. amygdalina leaf juice.